Enzyme immunoassays (EIA) for serodiagnosis of human leptospirosis: specific IgG3/IgG1 isotyping may further inform diagnosis of acute disease. - Elsa Fortes-Gabriel; Mariana Soares Guedes; Advait Shetty; Charles Klazer Gomes; Teresa Carreira; Maria Luísa Vieira; Lisa Esteves; Luísa Mota-Vieira; Maria Gomes-Solecki (Public Library of Science (PLoS), 2022)
The laborious microscopic agglutination test (MAT) is the gold standard serologic test for laboratory diagnosis of leptospirosis. We developed EIA based serologic assays using recombinant proteins (rLigA, rLigB, rLipL32) and whole-cell extracts from eight Leptospira serovars as antigen and assessed the diagnostic performance of the new assay within each class, against MAT positive (MAT+) human sera panels from Portugal/PT (n = 143) and Angola/AO (n = 100). We found that a combination of recombinant proteins rLigA, rLigB and rLipL32 correctly identified antigen-specific IgG from patients with clinical and laboratory confirmed leptospirosis (MAT+) with 92% sensitivity and ~ 97% specificity (AUC 0.974) in serum from the provinces of Luanda (LDA) and Huambo (HBO) in Angola. A combination of whole cell extracts of L. interrogans sv Copenhageni (LiC), L. kirschneri Mozdok (LkM), L. borgpetersenii Arborea (LbA) and L. biflexa Patoc (LbP) accurately identified patients with clinical and laboratory confirmed leptospirosis (MAT+) with 100% sensitivity and ~ 98% specificity for all provinces of Angola and Portugal (AUC: 0.997 for AO/LDA/HBO, 1.000 for AO/HLA, 0.999 for PT/AZ and 1.000 for PT/LIS). Interestingly, we found that MAT+ IgG+ serum from Angola had a significantly higher presence of IgD and that IgG3/IgG1 isotypes were significantly increased in the MAT+ IgG+ serum from Portugal. Given that IgM/IgD class and IgG3/IgG1 specific isotypes are produced in the earliest course of infection, immunoglobulin G isotyping may be used to inform diagnosis of acute leptospirosis. The speed, ease of use and accuracy of EIA tests make them excellent alternatives to the laborious and expensive MAT for screening acute infection in areas where circulating serovars of pathogenic Leptospira are well defined.